INFLUENCE OF AWARENESS, PERCEIVED IMPORTANCE, AND PERCEPTION TOWARD OTHERS ON INTENTION TO IMPLEMENT RESPONSIBLE TOURISM MARKETING - Ike Janita Dewi (JELAJAH: Journal of Tourism and Hospitality, 2019)
This research aims at examining influence of awareness and perceived importance on intention to implement responsible tourism marketing, moderated by perception towards other tourism stakeholders. Respondents of the research were 157 tourism Small and Medium Enterprises (SMEs) in Indonesia. Results show that while levels of awarenes and perceived importance were high, perception towards others and intention to implement responsible tourism marketing were lower. Further, awareness and perceived importance influenced positively intention to implement the concept. The influence of awareness on intention to implement was moderated by perception towards other stakeholders. This indicates that tourism industry is systemic where actions of stakeholders are highly interdependent. Individual stakeholder’s decision to adopt of a certain concept/strategy depends on others’ decision to also adopt it, despite the importance of such actions perceived by him/her individually.